Successful Consolidation/Maintenance Therapy with Single Agent Ibrutinib for Primary CNS Lymphoma after Initial Induction Therapy - Steven Du; Daniela Bota; Xiao-Tang Kong (MDPI AG, 2022)
Primary central nervous system lymphoma (PCNSL) is a rare and aggressive disease that originates from lymphocytes and develops in the central nervous system. There is no standard consolidation/maintenance therapy for PCNSL. While there exists a variety of options, the high chance of inferior outcomes for elderly patients and the risk of neurotoxicity requires exploration of alternative options for consolidation/maintenance therapy for PCNSL in the elderly population with CNS lymphoma. We treated one 77-year-old patient with single agent ibrutinib, a Bruton's tyrosine kinase inhibitor that crosses the blood-brain-barrier, as consolidation/maintenance therapy after induction therapy with high-dose methotrexate (HD-MTX) and rituximab plus temozolomide. This treatment resulted in good tolerance, further resolution of a small residue lymphoma, and sustained remission. The patient has completed one year of consolidation/maintenance therapy and is currently under clinical and imaging surveillance. She has survived 27 months without recurrence since diagnosis. This case shows the potential effectiveness of single agent ibrutinib as consolidation/maintenance therapy for PCNSL after induction therapy. More cases are needed to confirm the findings.